Spinal posture of thoracic and lumbar spine and pelvic tilt in highly trained cyclists - Muyor, J. M.; Lopez-Minarro, P. A.; Alacid, F. (Journal of Sports Science & Medicine, 2011)
The aim of this study was to evaluate sagittal thoracic and lumbar spinal curvatures and pelvic tilt in elite and master cyclists when standing on the floor, and sitting on a bicycle at three different handlebar-hand positions. A total of 60 elite male cyclists (mean age: 22.95 ± 3.38 years) and 60 master male cyclists (mean age: 34.27 ± 3.05 years) were evaluated. The Spinal Mouse system was used to measure sagittal thoracic and lumbar curvature in standing on the floor and sitting positions on the bicycle at three different handlebar-hand positions (high, medium, and low). The mean values for thoracic and lumbar curvatures and pelvic tilt in the standing position on the floor were 48.17 ± 8.05º, -27.32 ± 7.23º, and 13.65 ± 5.54º, respectively, for elite cyclists and 47.02 ± 9.24º, -25.30 ± 6.29º, and 11.25 ± 5.17º for master cyclists. A high frequency of thoracic hyperkyphosis in the standing position was observed (58.3% in elite cyclists and 53.3% in master cyclists), whereas predominately neutral values were found in the lumbar spine (88.3% and 76.7% in elite and master cyclists, respectively). When sitting on the bicycle, the thoracic curve was at a lower angle in the three handlebar-hand positions with respect to the standing position on the floor in both groups (p < 0.01). The lumbar curve adopted a kyphotic posture. In conclusion, cyclists present a high percentage of thoracic hyperkyphotic postures in standing positions on the floor. However, thoracic hyperkyphosis is not directly related to positions adopted on the bicycle